2005
DOI: 10.1177/104063870501700403
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Body Distribution, and Population Size of Malassezia Species in Healthy Dogs and in Dogs with Localized Cutaneous Lesions

Abstract: Abstract. Malassezia species are commensal organisms of human and animal skin that occasionally act as opportunistic pathogens. The lipid-dependent species are associated with human skin disorders, whereas the non-lipid-dependent species (Malassezia pachydermatis) is considered as an opportunistic secondary pathogen affecting the canine skin surface and ear canal. This study evaluated the relationship between Malassezia yeasts, their population size, and the occurrence of skin lesions from healthy and skin-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 27 publications
2
63
0
9
Order By: Relevance
“…In general, Malassezia yeasts are associated with the skin and mucous membranes in healthy and diseased dogs [9,10,22,30,31]. Even 62.9 % of the dogs are positive for Malassezia yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…In general, Malassezia yeasts are associated with the skin and mucous membranes in healthy and diseased dogs [9,10,22,30,31]. Even 62.9 % of the dogs are positive for Malassezia yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, cytologic evaluation identified Malassezia spp in 4 of 28 (14%) periocular samples obtained from eyes with blepharitis and 15 of 139 (11%) samples obtained from eyes without blepharitis. Because Malassezia spp were identified by fungal culture in that other study 3 and cytologic evaluation in the present study, the results of the 2 studies cannot be directly compared. Despite the fact that fungal culture is a more specific and sensitive method for identification of Malassezia spp than is cytologic evaluation, 3 we chose to use cytologic evaluation in the present study because it is used routinely in clinical practice and is easier to perform and less expensive than is a fungal culture.…”
Section: Discussionmentioning
confidence: 42%
“…3 Results of other studies 2,3 indicate that the likelihood of detection of Malassezia spp on the skin of dogs varies with the location of skin sampled, method used to detect the organism, and disease status of the patient. In the only other study 3 that assessed the frequency of Malassezia spp detection on the periocular skin of dogs, the organism was identified by fungal culture of swab specimens of the periocular area in 3 of 33 (9%) healthy dogs and 24 of 54 (44%) dogs with pruritic cutaneous lesions at various anatomic locations; however, it is unclear how many of those dogs with pruritic lesions were affected in the periocular region. In the present study, cytologic evaluation identified Malassezia spp in 4 of 28 (14%) periocular samples obtained from eyes with blepharitis and 15 of 139 (11%) samples obtained from eyes without blepharitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus pseudintermedius and Malassezia pachydermatis are the most common pathogens isolated from pyoderma and otitis externa in dogs (Cafarchia et al 2005;Fitzgerald 2009). In the last decade, resistance to antimicrobial agents has increased, particularly with the emergence and widespread dissemination of methicillin-resistant S. pseudintermedius in dogs as a result of the broad use of certain antimicrobial agents (Neu 1992;Kadlec and Schwarz 2013).…”
Section: Abstract: Natural Oil; Staphylococcus Pseudintermedius; Malamentioning
confidence: 99%